Does Non-Interest Income Make Banks More Risky? Retail Vs Investment Banking Activities In Africa - Ansah-Addo, L. (University of Ghana, 2015)
The study examines how increasing the shares of fees and commissions, trading income and total non-interest income makes African banks more risky, for banks that specialize in either retail or investment banking activities. The study used financial information obtained from the Bankscope database to construct a panel of African banks from 2008 to 2012. The study used the Ordinary Least Square (OLS) regression model with Newey – West standard errors, robust for heteroskedascity and autocorrelation. The findings indicate that when non-interest income interact with bank assets (size), it was revealed that as banks grow in size, they become more aggressive in their earnings and increase risk exposure from earning from fees and commissions’ income and trading income. Thus large banks must reduce earnings from non-interest activities; fees and commissions’ income and trading income, in order to reduce risks and become more stable. Smaller banks can also reduce risk and become more stable from increasing earnings from non-interest income. Findings along retail and investment activities indicated that trading income significantly increase risks and makes banks unstable for both retail and investment activities, because earnings for trading activities is based on speculations and are highly volatile. On the whole, the study found evidence to suggest that banks that diversify into fees and commissions’ income as well as trading income, in relation to their asset size, make banks more risky and increases the instability of the bank. For sustainable business practices, banks are advised to design new products for their retail activities, to enhance opportunities for generating fees and commissions’ income, in order to become more stable through income diversification.
Thesis(MPhil)
Keywords: fees; commission; Ordinary Least Square (OLS); bank assets; risk exposure